Survey of the Use of Phytosanitary Products in Vegetable Crops in the District of Abidjan, Côte d‘Ivore - Anne-Edwige Coulibaly; Gilles Alex Pakora; Ler-N’Ogn Dadé Georges Elisée Amari; Ako Aristide Berenger Ako; Joseph Allico Djaman (European Scientific Journal, ESJ, 2023)
The development of vegetable crops contributes to the food security of populations while reducing the problems of unemployment. However, these crops are subject to many pests that cause quantitative and qualitative damage to crops. To improve their yield, most market gardeners resort to the use of phytosanitary products. In order to take stock of the use of these products in the fight against pathogens of vegetable crops in the district of Abidjan, Côte d'Ivoire, a survey was carried out from January to February 2018 among 33 producers in the communes of Cocody and Port-Bouët. Twenty-seven pesticide trade names divided into 8 different families were identified. The majority of pesticides used were insecticides (53%) followed by fungicides (25%). Seventy-five percent (75%) of market gardeners were aware of the risk of pesticide toxicity, however, 53% of market gardeners did not use any means of protection during pesticide spraying. These bad practices jeopardize their health, that of consumers and the environment. It is therefore important to train and educate market gardeners on phytosanitary products and to provide them with adequate protective equipment.